2002
DOI: 10.1063/1.1455134
|View full text |Cite
|
Sign up to set email alerts
|

A high-density multichannel surface electromyography system for the characterization of single motor units

Abstract: An electromyography (EMG) system is presented that noninvasively records the electrical activity of a muscle with 126 densely spaced skin-surface electrodes. The electrodes are arranged in a two-dimensional array and integrated in a single container for ease of application. Signals are recorded “monopolarly”, with a reference electrode placed at a distance from the array. With this recording configuration, the surface EMG (sEMG) potential distribution can be described not only as a function of time, but also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
89
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 32 publications
0
89
0
Order By: Relevance
“…Extracting independent information from a set of surface EMG signals might be used to obtain most of the separate MU-potentials. Along this line, we have already shown that using principal component analysis (PCA) for the removal of common information from a set of signals collected with a high-density EMG (HD-EMG) grid [8], [9] can improve EMG-based muscle force estimation [1]. Manuscript Surface EMG is always contaminated by common sources (volume conduction), at least to some degree.…”
Section: Introductionmentioning
confidence: 99%
“…Extracting independent information from a set of surface EMG signals might be used to obtain most of the separate MU-potentials. Along this line, we have already shown that using principal component analysis (PCA) for the removal of common information from a set of signals collected with a high-density EMG (HD-EMG) grid [8], [9] can improve EMG-based muscle force estimation [1]. Manuscript Surface EMG is always contaminated by common sources (volume conduction), at least to some degree.…”
Section: Introductionmentioning
confidence: 99%
“…Electrodes were placed on the first dorsal interosseus (FDI) of the right hand in a ''belly-tendon'' arrangement, following standard skin preparation. The signal was continuously monitored, amplified (ActiveOne amplifier; BioSemi, Amsterdam, The Netherlands), bandpass filtered (10-500 Hz), digitized (2048 samples/sec), and stored for off-line analysis using MyoDAQ software (Blok, van Dijk, Drost, Zwarts, & Stegeman, 2002).…”
Section: Electromyographymentioning
confidence: 99%
“…Accurate discrimination of FPs is possible with needle electrodes, but it is difficult to obtain long and stable recordings of a sufficient number of FPs. We decided to use high-density surface EMG 21,22 to record FPs in patients with ALS. The multielectrode grid provides a spatial resolution sufficient to differentiate FPs arising in the same muscle but from different MUs.…”
mentioning
confidence: 99%
“…Electrodes were arranged in a 10 ϫ 13 rectangular matrix with an interelectrode distance of 5 mm. 21 The grid was placed over the belly of the biceps brachii muscle (seven patients) or the lateral vastus muscle (three patients), parallel to the muscle fibers. The monopolar EMG signals, each referenced to the olecranon or to the patella, were amplified, band-pass filtered (3 to 400 Hz), analog-digital converted with a resolution 0.5 V/bit at a rate of 2,000 samples/second/channel, and stored on the hard disk of a personal computer for off-line processing.…”
mentioning
confidence: 99%